Psychological aspects of pain assessment - Sargautytė, R. (Psichologija, 1993)
Pain is the most common symptom that leads patients to seek medical help. This paper reviews selected areas of current knowledge and personal experience about pain expression and measurement. Question is raised about the usefulness of the distinction between organic and psychogenic pain patients, psychological conceptions of pain are presented. The peculiarities of pain and clinical pain are stressed. As the psychologists become more and more involved in evaluation and treatment of pain patients, their role should be defined more precisely.